Views of Bangladeshi Medical Students’ on teacher’s evaluation. (Bangladesh Journal of Medical Education, 2024)
Teacher evaluation (TE) is systematic, periodic evaluation of a teacher with respect to his/her performance on job and his/her potential for development. This descriptive type of cross sectional study was conducted to explore the views of the students regarding the ways and means for implementing medical teachers’ evaluation in Bangladesh. Study period was from July 01, 2022 to June 30, 2023, conducted at four governments and four non-government medical colleges selected conveniently. Medical students were enrolled conveniently. Total sample size was 866 medical students. Data were collected through self-administered semi-structured questionnaire from students. Study revealed that majority of the students (95.4%) were in favor of TE. Majority (85%) students were in favor of anonymous evaluation and 49% students opined for both offline or/and online and 40% for offline evaluation. Areas to be evaluated are teacher’s teaching performance and depth of knowledge, communication with students, classroom control, quality of teaching materials with a number of other areas. Sources of information for TE, in order to preferences are student, trained evaluator, senior teacher, self and peer with highest weightage given to students rating. Study recommended that TE should be initiated, within the course, anonymous, may be from multiple sources.   BJME, Volume-15, Issue-02, July 2024: 36-51